Managing Bilateral Congenital Cataracts in Early Childhood: A Clinical and Surgical Perspective - Imelda, Eva; Lathifah, Lakaeisya SY; Lubis, Dara Amalia; Toshniwal, Nikhil; Adev, Sarra Mutiara (Heca Sentra Analitika, 2025)
Congenital cataract is a leading cause of childhood blindness that demands prompt surgical intervention to prevent irreversible visual impairment. This case report presents an infant with bilateral congenital cataracts whose diagnosis and treatment were delayed beyond the optimal intervention window. The patient underwent cataract extraction using irrigation aspiration, primary posterior capsulotomy, and anterior vitrectomy. Intraocular lens (IOL) implantation was deferred due to considerations of the patient’s age and corneal diameter, and aphakia was managed with high-powered spectacles. Postoperative follow-up revealed improved visual responses, including fixation and following of light and objects, indicating positive visual development. This case highlights the importance of timely identification, appropriate surgical technique, and tailored postoperative visual rehabilitation in managing pediatric cataracts to optimize functional outcomes.